Peningkatan Kompetensi Mahasiswa di Bidang Network Computer dan Cyber Security melalui Program Studi Independen Merdeka Belajar Kampus Merdeka - Ade Sarah Huzaifah (CV. Aksara Global Akademia, 2024)
Proficiency in computer networking and cybersecurity has become very important, especially with the increasing need for human resources in this sector. However, the availability of experts remains scarce due to the complexity of technology, demands for extensive knowledge and skills, and limitations in education and training. The Merdeka Belajar Kampus Merdeka (MBKM) programme initiated by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia offers a solution through independent study to improve student competencies. This programme aims to provide learning flexibility, encourage independent learning, and improve student’s technical skills and soft skills. This article discusses efforts to improve interdisciplinary student competencies in computer networking and cybersecurity through the MBKM independent study programme, especially through Magang Studi Independen Bersertifikat (MSIB). As a Programme Assistance Lecturer (DPP), the author used a qualitative approach with a case study method involving students from various study programmes. The results of the activities show that the MSIB programme has a positive impact on improving student competencies across disciplines, both in technical skills such as network configuration and security analysis, as well as in the development of soft skills such as time management, communication, critical thinking, and teamwork.